PERANCANGAN SISTEM INFORMASI PENGGAJIAN KARYAWAN BERBASIS WEBSITE DI PERUSAHAAN X MENGGUNAKAN METODE PROTOTYPE - Deri Ramadiyan Hidayat; Dani Hamdani (LPPM Universitas Abdurrab, 2024)
Company X is a growing company along with increasing customer demand and employee needs, which means a computerized system is needed to reduce errors in salary calculations. Currently the company is still less effective in calculating employee salaries because it still calculates, pays salaries and makes reports manually with methods in data collection, namely using interviews with company owners, conducting field observations and also questionnaires used for assessment of system design, the design method uses prototypes which have stages, namely listening to customers or collecting needs, Design and Test in assessment The trial uses a System Usability Scale (SUS) assessment of the respondent's assessment data, then calculates using the formula from the System Usability Scale, the smallest value is 78 and the largest value is 90 from the depalan respondent by answering 10 questions which has an average score of 86 from the qualifications in the table above